2006
DOI: 10.1111/j.1365-2893.2005.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations affecting the replication capacity of the hepatitis B virus

Abstract: The genetic variability of the hepatitis B virus (HBV) encounters two compounding forces: a high viral copy number produced during active replication and the lack of proofreading activity in the HBV polymerase, resulting in a high mutational rate. A large pool of quasispecies is generated in which the fittest virus, i.e. the virus that replicates best, becomes the dominant species. Immune and antiviral selection pressures result in vaccine/immunoglobulin escape mutants and antiviral resistant variants. Viruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 71 publications
4
106
1
4
Order By: Relevance
“…This enhanced replication might be associated with HBV DNA‐titer flare‐up in this case. This mutation is also detected in ADV‐resistant cases,35, 36 although in vitro analysis revealed that this mutation is not associated with ADV resistance.…”
Section: Discussionmentioning
confidence: 96%
“…This enhanced replication might be associated with HBV DNA‐titer flare‐up in this case. This mutation is also detected in ADV‐resistant cases,35, 36 although in vitro analysis revealed that this mutation is not associated with ADV resistance.…”
Section: Discussionmentioning
confidence: 96%
“…Posteriormente, a mutação rtA181T/V/S também foi relacionada com redução da susceptibilidade viral a esse NA (223,227,228). Além dessas mutações, diversas mutações compensatórias em diferentes domínios da RT já foram identificadas em cepas com resistência à lamivudina: rtL80V/I, rtV173L, rtL180M/C (223, 228), rtA200V (229), rtV/F/L/M207I (230), rtQ215S (231,232), rtL217P e rtL229F (233).…”
Section: Mutações No Gene Punclassified
“…A resistência ao adefovir foi inicialmente caracterizada pelas mutações rtA181V/T (domínio B) e/ou rtN236T (domínio D) (223,226,232 (228,232), rtN238T/D/R, rtT240Y, rtN248H (228,232,238).…”
Section: Mutações No Gene Punclassified
“…Mutations associated with NUCs treatment can cause changes to the surface antigen (HBsAg) protein of HBV, thus forming antiviral drug-associated potential vaccine-escape mutants (ADAPVEMs); therefore, antibodies directed against the HBsAg protein may not neutralize the virus (12). Consequently, these changes result in (i) the reactivation of HBV in previously anti-HBs immune persons, (ii) problems during diagnosis, and (iii) failure of infection prevention, either with vaccination or hepatitis B immunoglobulin (HBIg) (9).…”
Section: Introductionmentioning
confidence: 99%
“…Antiviral drug resistance is defined as the reduced susceptibility of a virus to the inhibitory effect of a specific drug. Two types of antiviral resistance mutations have been identified, namely, primary resistance mutations, which are directly responsible for the associated drugresistance, and secondary or compensatory mutations, which increase the replicative capacity of the virus (9,10). In addition, it is important to keep in mind that the HBV polymerase ( pol ) gene completely overlaps with the envelope (S) gene (11).…”
Section: Introductionmentioning
confidence: 99%